Optimization of barrel vault surfaces using energetic potential method - Sadowski, Kajetan (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
The energy certification, introduced in 2009, enables interested parties or organizations to analyze the data developed during the preparation of energy performance certificates or the proposed energy performance of a building. Through comparatitive analysis, trends can be described using the criteria for shaping them as needed. The author has made selected analyzes focusing on residential housing in the division of single family and multi-family housing. Obtained results indicate the existing and expected trends related to the reduction of fossil fuel consumption but also show their slow pace and in some cases even no change. The conclusions drawn show the reasons for a certain rate of change, enabling them to undertake actions supporting certain tendencies or initiating them. As part of this work, the author analyzed selected indicators on the basis of their 168 energy certificates of residential buildings in 2014−2017.